Design selective band antenna using coupling sidewall and multi resonator for wireless communications - Ali Khalid Jassim; Malik Jasim farhan; Alaa Fadhil Fahad (Bulletin of Electrical Engineering and Informatics, 2020)
Design and simulation of antenna with performance operating at bandwidth (4.5-6.5) GHz, with center frequency 5.5 GHz. This antenna constriction from two cylindrical antenna shapes and four cylindrical resonators with include iris to matching impedance, to enhancement sharp edge band and four tuned between coupling sidewall to removed distortions. Improving the frequency selection of the bandwidth requirement antenna is by adjusting the cylinder length of the antenna The proposed antenna is operating ideal filter because the edge of the band rejection is matched the edge of the bandwidth requirement which makes it perform well including broad edges for the band rejection and sharp edges of the bandwidth requirement together with a little insertion between two types and good return loss of the bandwidth requirement. CST software used to investigate and simulated results.